(untitled) (Web of Teachers: Inderscience Research, 2023)
This article presents the etymology of international words used in our life in English, Russian and Uzbek languages. Languages differ in structure, vocabulary, but all languages have some common laws. Some foreign words that we often hear and use in our own and other languages are of foreign origin and borrowed from other languages.